The Effect of Green Human Resource Management in Encouraging Green Team Creativity and Organizational Sustainability - Adityo Nugroho; Yasmine Nasution (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Sustainability pressures are intensifying in the fossil-based energy sector, requiring organizations to strengthen human resources practices that support environmental goals. This study examines the roles of Green Human Resource Management (GHRM) in enhancing organizational sustainability and green team creativity, while also considering top management support and environmental orientation as antecedents shaping GHRM. A quantitative approach is conducted using a perception-based survey of permanent employees in a large energy sector company in Indonesia. The data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that top management support and environmental orientation positively influence GHRM, while GHRM has a strong impact on green team creativity and organizational sustainability. Green team creativity also positively impacts organizational sustainability. These findings highlight GHRM as an organizational system that fosters green team creativity and strengthens organizational sustainability from employees’ perspectives. It provides empirical evidence from the Indonesian energy sector and highlights the importance of integrating top management support, environmental orientation, and green human resource management to advance organizational sustainability.